2018
DOI: 10.1016/j.clinbiochem.2018.04.020
|View full text |Cite
|
Sign up to set email alerts
|

Order of draw practices in venous blood sampling at clinical biochemistry departments in the Danish health care system

Abstract: Venous order of draw procedures is diverse at Danish clinical biochemistry departments and show moderate adherence to international guidelines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 14 publications
(14 reference statements)
0
5
0
Order By: Relevance
“…For the last two regions, the approach to disinfection or not was more mixed. Our previous study found that standardization between laboratories was poor (order of draw) [ 4 ] Our current study shows that there is a mismatch between local practices and international scientific literature and guidelines. Perhaps now, with the Danish bachelor's degree for BLS being more rooted in research and science since 2013 [ 32 ], new generations of BLS that we educate may find it more natural to update local practices with the newest scientific literature.…”
Section: Discussionmentioning
confidence: 85%
See 3 more Smart Citations
“…For the last two regions, the approach to disinfection or not was more mixed. Our previous study found that standardization between laboratories was poor (order of draw) [ 4 ] Our current study shows that there is a mismatch between local practices and international scientific literature and guidelines. Perhaps now, with the Danish bachelor's degree for BLS being more rooted in research and science since 2013 [ 32 ], new generations of BLS that we educate may find it more natural to update local practices with the newest scientific literature.…”
Section: Discussionmentioning
confidence: 85%
“…Denmark does not have its own standardized national recommendations for the disinfection procedure when drawing blood for p-ethanol. We have previously shown that Danish laboratories typically develop their own local protocols and that national laboratory guidelines are not custom in our country [ 4 ]. If interlaboratory guidelines exist, they are regional based, as shown in this study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The Seventh Edition of the Clinical and Laboratory Standard Institute (CLSI) suggested that the order of draw sequence should start with blood culture or sterile tubes, followed by plain or gel tubes and then tubes containing additives, namely, the heparin tubes, ethylenediaminetetraacetic acid (EDTA) tubes, and the glycolytic inhibitor or fluoride tubes [26]. The purpose is to reduce the carryover of additive contamination, which can lead to erroneous results [26,27]. EDTA contamination, for example, can cause spurious hyperkalemia and hypocalcemia secondary to the EDTA chelation effect [22,28].…”
Section: Order Of Drawmentioning
confidence: 99%